2015
DOI: 10.1002/stem.2254
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Interleukin 1 Receptor Antagonist Promotes Macrophage Polarization and Inhibits B Cell Differentiation

Abstract: The role of interleukin 1 receptor antagonist (IL1RA) in mediating the immunosuppressive effect of mesenchymal stem/stromal cells (MSCs) has been reported in several studies. However, how MSC-derived IL1RA influences the host response has not been clearly investigated. We therefore derived MSCs from the bone marrow of IL1RA knockout mice and evaluated their immunosuppressive effect on different immune cell subsets. IL1RA deficient (IL1RA 2/2 ) or wild type (wt) MSCs inhibited to the same extend the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
150
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(159 citation statements)
references
References 42 publications
7
150
1
1
Order By: Relevance
“…Immunomodulatory role of murine BM-MSCs was reported to be dependent on the expression of IL-6-dependent PGE2, IL1-RA and glucocorticoid-induced leucine zipper (GILZ) while inducible nitric oxide synthase (iNOS) expression was dispensable [49,50,51]. However, some studies failed to demonstrate any improvement with MSC treatment, probably related to mouse strain genetic background, or use of immortalized murine MSCs [52,53,54].…”
Section: Mesenchymal Stem Cells and Rheumatic Diseasesmentioning
confidence: 99%
“…Immunomodulatory role of murine BM-MSCs was reported to be dependent on the expression of IL-6-dependent PGE2, IL1-RA and glucocorticoid-induced leucine zipper (GILZ) while inducible nitric oxide synthase (iNOS) expression was dispensable [49,50,51]. However, some studies failed to demonstrate any improvement with MSC treatment, probably related to mouse strain genetic background, or use of immortalized murine MSCs [52,53,54].…”
Section: Mesenchymal Stem Cells and Rheumatic Diseasesmentioning
confidence: 99%
“…One of their key immunomodulatory factors is indoleamine 2,3-dioxygenase (IDO), which deprives the environment of L-tryptophan thereby inhibiting lymphocyte proliferation [18], has been demonstrated to promote graft acceptance after solid organ transplantation [19]. In addition, prostaglandin E 2 (PGE 2 ), CCL2 and interleukin 1 receptor antagonist (IL1RA), which are produced by MSC have shown to have an important role in the therapeutic effects of MSC on autoimmune diseases, such as rheumatoid arthritis [3, 4, 2023]. Besides secretion of anti-inflammatory factors, MSC express cell surface proteins that are known for their immunoregulatory function, such as programmed death-ligand 1 (PD-L1), which inhibits lymphocyte proliferation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, MSCs inhibit the activation of dendritic cells (DCs), proinflammatory M1-like macrophages, natural killer (NK) cells, and B and T cells while inducing the generation of cells with anti-inflammatory phenotypes [1518]. Based on these broad immunomodulatory abilities, the therapeutic potential of MSCs in autoimmune and inflammatory disorders has been intensively investigated in experimental mouse models [1923].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…TSG-6 will then prevent the interaction of the Toll-like receptor 2 (TLR-2) on macrophages by interacting with their CD44 receptor and thus modulate TLR-2-mediated NF- κ B signaling and decrease macrophage inflammatory response [44]. We and others have shown that IL-1 receptor antagonist (IL-1RA) produced by MSCs is involved in the modulation of the plasticity of macrophages promoting their differentiation toward an M2 phenotype [18, 45]. …”
Section: Innate Immunity In Ra and The Effect Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation